Knowledge and perception of senior year pharmacy students about generic medicines in public Universities of Malaysia - Shi Wei Lee; Mohamed Azmi Hassali; Asrul Akmal Shafie (Archives of Global Professionals, 2014)
Objective: The aims of this study were to evaluate senior year pharmacy students' perceptions of and knowledge about generic medicines and generic substitution and to explore factors influencing these students' future generic substitution practices. Materials and Methods: The study was conducted among third year pharmacy students studying at five public pharmacy schools located in Malaysia. A pre-validated self-administered questionnaire was used to collect the data. The questionnaire was distributed via collaborating lecturers at their respective universities after a normal class session and recollected on the same day. In addition to the descriptive analysis, inferential statistics were used to determine the association among study variables. SPSS v 17.0 was used for data analysis. Results: A total of 364 students from five different universities offering pharmacy course in Malaysia responded to the survey. Females subjugated the group (n=284, 78.0%) with mean age being 24.48±0.97 years. In response to the regulatory limits for the ratio of the areas under the plasma drug concentration versus time curves and the maximum plasma drug concentrations, only 11 (3.0%) of the respondents correctly identified the regulatory limits. Students reported mixed perceptions towards the efficacy, safety and comparability of generic medicines. Major limitations were seen whereby participants demanded more information towards safety issues of generic medicines hence reported lack of confidence in their ability of brand switching. Majority of the respondents insisted that they require additional information of bioequivalence testing were in favor that an audio/visual educational package will help them in understanding the concepts of bioequivalence and bioavailability in a much progressive manner. Conclusion: The findings highlight that pharmacy students needs a better understanding of the principles and concepts of bioavailability and bioequivalence if they are to contribute appropriately to generic medicine use.